Iraq: more challenges ahead for a fractured humanitarian enterprise - Hansen, Greg (Tufts Archival Research Center, 2005)
The report draws upon five years of active monitoring in Iraq and the region, a relatively long period in which agencies have had many opportunities to adapt to a difficult context. The author argues that despite some improvements in security for Iraqis, the ability of the international community to provide for the most vulnerable is impaired by the continued politicization of humanitarian response and systemic deficiencies in coordination mechanisms.